Transition to attack in elite soccer - Hughes, M.; Lovell, T. (Journal of Human Sport & Exercise, 2019)
Since the pioneering work of Reep and Benjamin (1968) on regained possessions, there has been a lack of detailed, informative research in the area. The aim of this study was to analyse all elements of transitions to attack in elite football. The influence of turnover zone, turnover type and `on the ball` player actions upon scoring goals and creating scoring opportunities (S.O.`s) were examined. A total of 3,077 transitions from all 29 games of the 2014-15 Champion`s League knockout stages were coded. Multidimensional qualitative data using 11 ordered categorical variables were obtained to characterise each transition. Data were analysed using chi-square analysis. Winning turnovers in offensive areas increased the chance of scoring a goal and creating a S.O. (p < .001). Nearly half of all turnovers in the offensive zone, 49.45% (n=45) resulted in a S.O., and 7.69% (n=7) lead to goals. The tackle was the most productive way to turnover the ball (p < .05). Teams created significantly more S.O.s and scored more goals when the first and second actions after the turnover were forward (p < .05); successful dribbles, runs with the ball and long passes were the optimal player actions. Further analysis revealed that successful teams (top 4) created more S.O.`s from the defensive, defensive midfield and offensive midfield but not the offensive zone (p < .01). Finally teams created more S.O.s from turnovers in the offensive half, but not the defensive half, when losing or drawing the tie (p < .05). It was concluded that teams should press high to win turnovers and create S.O.`s, supporting the findings of Reep and Benjamin (1968). It was further concluded that the immediate player actions after winning the turnover are critical to the outcome of the transition.